Folic acid intervention changes liver Foxp3 methylation and ameliorates the damage caused by Th17/Treg imbalance after long-term alcohol exposure. Issue 9 (19th April 2022) - Zhao, Huichao; Guo, Peiyu; Zuo, Yuwei; Wang, Yanhui; Zhao, Hui; Lan, Tongtong; Xue, Meilan; Zhang, Huaqi; Liang, Hui
Abstract : Folic acid prevented ethanol-induced skewed hepatic Th17/Treg balance and inflammation by inhibiting DNMT3a expression and reducing the methylation rate of Foxp3 DNA, which in turn upregulated the Treg frequency. Figure created with BioRender.com. Abstract : Folic acid, as a key source of methyl donor in DNA methylation, has been proved to play a beneficial role in inflammation modulation, which is usually impaired in alcoholic liver disease (ALD). However, the role of folic acid in alcoholic liver inflammation and injury remain elusive. In this study, we sought to uncover the potential protective mechanism by which folic acid ameliorates alcoholic liver injury. 100 male C57BL/6J mice were randomly divided into 5 groups: normal saline group, folic acid control group (5 mg per kg BW), ethanol model group (56% v/v, 10 mL per kg BW), folic acid + ethanol group, and 5-Aza + ethanol group (0.1 mL per 20 g BW). Liquor (10 mL per kg BW) was orally administered 1 h after the folic acid treatment for 10 consecutive weeks. The results showed that folic acid-inhibited ethanol-induced serum TG, TC, and LDL elevation attenuated hepatic fat accumulation and maintained ALT at a normal level. 10 weeks of ethanol administration simultaneously upregulated the hepatic proportion of Th17 and Treg cells to different extents and broke the homeostasis of liver immunization. Folic acid limited ethanol-induced inflammatory injury by increasing the frequency of hepatic Treg cells. Importantly, this effect may be caused by decreased DNMT3a, which in turn downregulates the methylated levels of CPG2 and CPG3 in the Foxp3 promoter region, changing the abundance of Foxp3 expression and improving the Th17/Treg imbalance. In summary, our findings demonstrated that folic acid supplementation may relieve ethanol-induced Th17/Treg disbalance through altering Foxp3 promoter methylation patterns, suggesting that folic acid may be a feasible preventive strategy for ALD.